Corn peptides ameliorate nonalcoholic fatty liver disease by suppressing endoplasmic reticulum stress via the AMPKα/Sirt1 pathway in vivo and in vitro. (June 2022) - Yao, Zhicui; Song, Shiming; Li, Xiaoling; Wang, Wentao; Ren, Peng; Wang, Haiyue; Xie, Ying; Li, Zengning
Graphical abstract: Highlights: CPs contain a large number of antioxidant peptides, as determined by LC-MS/MS. CPs suppressed ER and oxidative stress via AMPKα/Sirt1 signaling pathway in NAFLD. CPs effectively ameliorated lipid metabolism in NAFLD in vitro and in vivo . CPs have great potential as green functional molecules for preventing NAFLD. Abstract: Corn peptides (CPs) are a novel food obtained from the enzymatic hydrolysis of corn gluten meal. Recent studies indicate the hepatoprotective ability of CPs. However, little is known about the effect of CPs on nonalcoholic fatty liver disease (NAFLD). The aim of this study was to investigate the effect of CPs in NAFLD and to decipher the underlying mechanisms. We show that CPs contain large number of antioxidant peptides. They significantly ameliorated oxidative and endoplasmic reticulum stress, and downregulated lipid metabolism-related proteins in in vivo and in vitro models. The AMPKα/Sirt1 pathway was activated by CPs, as was evident through the incubation of cells with the AMPK inhibitor, Compound C. These results demonstrate that CPs could be a promising functional food for preventing NAFLD progression, at least in part through activation of the AMPKα/Sirt1 pathway.